Analisis Faktor Pemahaman UMKM terhadap Standar Akuntansi Keuangan Factor Analysis of MSME Understanding of Financial Accounting Standards - Ni’immas Ni’immas (EBBANK, 2022)
MSMEs are an important aspect for the economic development of a country. However, SMEMs are faced with financial reporting problems. Meanwhile, financial reporting is important for SMEMs, both for making decisions and as a standard for the feasibility of access to capital. This study aims to examine the factors that influence the perception of SMEM actors on financial reporting, the factors that influence the acquisition of SMEM loans and the factors that influence the understanding of SMEM actors towards Financial Accounting Standards. A total of 100 samples of SMEM actors were randomly selected to represent the MSME population in Yogyakarta. This study uses a quantitative approach with statistical regression analysis. This study finds that the understanding of SMEMs in Yogyakarta on Accounting Standards is still very limited.